Complete chloroplast genome sequence of Bambusa rigida (Bambuseae). Issue 3 (2nd July 2020) - Zheng, Ying; Hou, Dan; Zhuo, Juan; Zheng, Renhong; Wang, Yong; Li, Benxiang; Yu, Xuejun; Lin, Xinchun
Abstract: Bambusa rigida is a tropical woody bamboo widely distributed in Sichuan and southeastern of China with important economic and ecological values. We performed a complete chloroplast (cp) genome of B . rigida using Illumina NovaSeq PE150 platform. The length of complete cp sequence is 139, 500 bp in size with a pair of inverted repeat (IR) regions of 43, 587 bp, which separates a large single-copy (LSC) region of 83, 036 bp and a small single-copy (SSC) region of 12, 875 bp. Plastid genome contains 132 genes, including 84 protein-coding genes, 40 tRNA genes, and 8 rRNA genes. Phylogenetic analysis based on 30 cp genomes indicates that B. rigida is closely related to Bambusa ventricosa in Bambuseae.